2022
DOI: 10.1182/blood.2020007932
|View full text |Cite
|
Sign up to set email alerts
|

MondoA drives malignancy in B-ALL through enhanced adaptation to metabolic stress

Abstract: Cancer cells are in most instances characterized by rapid proliferation and uncontrolled cell division. Hence, they must adapt to proliferation-induced metabolic stress through intrinsic or acquired anti-metabolic stress responses to maintain homeostasis and survival. One mechanism to achieve this is to reprogram gene expression in a metabolism-dependent manner. MondoA (also known as MLXIP), a member of the MYC interactome, has been described as an example of such a metabolic sensor. However, the role of Mondo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…These studies supported the idea that MondoA maintains a differentiation block in ALL blasts. Consistent with this finding, a subsequent study showed leukemic blasts with the highest levels of MondoA were associated with shorter survival [ 95 ].…”
Section: Mondoasupporting
confidence: 63%
See 1 more Smart Citation
“…These studies supported the idea that MondoA maintains a differentiation block in ALL blasts. Consistent with this finding, a subsequent study showed leukemic blasts with the highest levels of MondoA were associated with shorter survival [ 95 ].…”
Section: Mondoasupporting
confidence: 63%
“…They tend to encode enzymes involved in carbohydrate and lipid metabolism; mitochondrial and ribosomal proteins and factors that regulate translational initiation, elongation and termination [ 31 , 39 , 41 , 42 , 46 , 70 , 71 , 72 , 73 , 76 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Together, these findings indicate that, via selective, cytoplasmic-nuclear partitioning, sharing of Mxd1,4 and Mnt and binding to both common and unique target genes, this “Extended Myc Network” cross-talks, while simultaneously communicating with and responding to the metabolic cues and reservoirs needed to support energy-intensive processes such as translation and proliferation [ 36 , 42 , 64 , 65 , 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies supported the idea that MondoA maintains a differentiation block in ALL blasts. Consistent with this finding, a subsequent study showed leukemic blasts with the highest levels of MondoA were associated with shorter survival [84].…”
Section: Mondoasupporting
confidence: 60%
“…They tend to encode enzymes involved in carbohydrate and lipid metabolism; mitochondrial and ribosomal proteins and factors that regulate translational initiation, elongation and termination [21,33,50,[57][58][59][60]63,[65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Together these findings indicate that, via selective, cytoplasmic-nuclear partitioning, sharing of Mxd1,4 and Mnt and binding to both common and unique target genes, this "Extended Myc Network" cross-talks, while simultaneously communicating with and responding to the metabolic cues needed to support energy-intensive processes such as translation and proliferation [43,[50][51][52]56,[77][78][79][80][81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 86%
“…The extracellular acidification rate (ECAR), a measure of glycolysis, and oxygen consumption rate (OCR) were determined using an XF96 Extracellular Flux Analyzer (Seahorse Bioscience) as described. 23 …”
Section: Methodsmentioning
confidence: 99%